Analysis of Torquetenovirus DNA levels in NSCLC patients treated with immune checkpoint inhibitors - Lilia Cinti; Lucrezia Tuosto; Piergiorgio Roberto; Roberta Campagna; Aurelia Rughetti; Chiara Napoletano; Alain J. Gelibter; Daniele Santini; Guido Antonelli; Ombretta Turriziani (PLoS ONE, 2026)
In recent years, Torquetenovirus (TTV) load has emerged as a potential biomarker of immune competence across various clinical contexts, albeit its significance in cancer patients undergoing immunotherapy remains largely unexplored. This study aimed to investigate the level of TTV viral load in non-small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors (ICIs). A total of 64 NSCLC patients were enrolled. Serum TTV DNA levels were quantified by real-time PCR at baseline (T0) and after three months of ICI therapy (T1). As control, TTV levels were also measured in a cohort of healthy donors at a single time point. Statistical analyses were performed to compare TTV copy numbers across groups and time points. At baseline, cancer patients exhibited significantly higher TTV viral loads than healthy donors, consistent with an immunocompromised status. Following ICI treatment, a significant decline in TTV levels was observed in the oncologic cohort, reaching values comparable to those of healthy individuals, with a more pronounced decrease observed in patients responsive to therapy. This study provides the first evidence that TTV viral load decreases following immunotherapy in NSCLC patients, potentially reflecting a restoration of immune competence. These findings support the hypothesis that TTV monitoring could serve as a surrogate marker of immune function during ICI treatment. Further large-scale, longitudinal studies are warranted to validate its clinical meaning in oncologic settings.